PID optimal control to reduce energy consumption in DC-drive system - Hari Maghfiroh; Muhammad Nizam; Supriyanto Praptodiyono (Institute of Advanced Engineering and Science, 2020)
The control system that is widely used in industry is PID (Proportional Integral Derivative). Almost 90% of industries still use PID control systems because of its simplicity, applicability, and reliability. However, the weakness of PID is that it takes a long time to tune. PID control with good performance and low energy consumption can be achieved using GA tuning with the appropriate objective function. The contribution of this paper is to propose the implementation of LQR control in the form of PID using GA tuning with LQR objective function. The proposed algorithm was implemented both in the simulation and hardware which is a mini conveyor with a DC motor. The result shows that the proposed algorithm is better in both IAE and energy consumption compared with other PID tuning, Ziegler–Nichols (ZN), and GA with IAE objective function. Compared with PID ZN, it has IAE and energy reduction by 2.76% and 16.07% respectively. Although its performance is lower than the LQR, it has other advantages that use fewer sensors. The other advantage of the proposed method is, PID is more familiar using. Therefore, it easy to be implemented in the existing system without a lot of changes.